THE INFLUENCE OF PSYCHOLINGUISTIC PROCESSES ON LANGUAGE DEVELOPMENT IN EARLY CHILDHOOD - Tampubolon, Diana Dian Sari; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
This study investigates how psycholinguistic processes contribute to language development, with a particular focus on cognitive aspects such as memory, perception, and attention. The research explores the complex interactions between these cognitive processes and how children and adults alike learn and understand language. Additionally, it examines how external factors, such as social environments and interactions, impact these psycholinguistic processes, ultimately shaping language skills and comprehension. Using a combination of experiments and longitudinal observations, this study identifies key stages in the development of language and underscores the importance of neurocognitive development in achieving linguistic proficiency. The findings offer detailed insights into how psycholinguistic processes are vital to learning both a first and a second language.